Tracking elevated pollution layers with a newly developed hyperspectral Sun/Sky spectrometer (4STAR): Results from the TCAP 2012 and 2013 campaigns. Issue 5 (5th March 2014) - Segal‐Rosenheimer, M.; Russell, P. B.; Schmid, B.; Redemann, J.; Livingston, J. M.; Flynn, C. J.; Johnson, R. R.; Dunagan, S. E.; Shinozuka, Y.; Herman, J.; Cede, A.; Abuhassan, N.; et al.
Abstract Total columnar water vapor (CWV), nitrogen dioxide (NO2), and ozone (O3) are derived from a newly developed, hyperspectral airborne Sun‐sky spectrometer (4STAR) for the first time during the two intensive phases of the Two‐Column Aerosol Project (TCAP) in summer 2012 and winter 2013 aboard the DOE G‐1 aircraft. We compare results with coincident measurements. We find 0.045 g/cm2 (4.2%) negative bias and 0.28 g/cm2 (26.3%) root‐mean‐square difference (RMSD) in water vapor layer comparison with an in situ hygrometer and an overall RMSD of 1.28 g/m3 (38%) water vapor amount in profile by profile comparisons, with differences distributed evenly around zero. RMSD for O3 columns average to 3%, with a 1% negative bias for 4STAR compared with the Ozone Measuring Instrument along aircraft flight tracks for 14 flights during both TCAP phases. Ground‐based comparisons with Pandora spectrometers at the Goddard Space Flight Center, Greenbelt, Maryland, showed excellent agreement between the instruments for both O3 (1% RMSD and 0.1% bias) and NO2 (17.5% RMSD and −8% bias). We apply clustering analysis of the retrieved products as a case study during the TCAP summer campaign to identify variations in atmospheric composition of elevated pollution layers and demonstrate that combined total column measurements of trace gas and aerosols can be used to define different pollution layer sources, by comparing our results with trajectory analysis and in situ airborne miniSPLAT (single‐particle mass spectrometer) measurements. Our analysis represents a first step in linking sparse but intense in situ measurements from suborbital campaigns with total column observations from space.